EFFECT OF PHOTOPERIOD ON INTESTINAL MICROBIOTA AND CIRCADIAN RHYTHM, AND ITS INFLUENCE ON PERFORMANCE, THE IMMUNE SYSTEM AND THE WELFARE OF BROILER CHICKENS (Veterinária Notícias, 2021)
The intestinal microbiota of poultry is still understudied, filled with knowledge gaps. However, the microbiota may act directly on the host health, being highly dependent on several factors, such as the light. In 2020, poultry meat has become the most consumed animal protein worldwide, followed by increasing consumers' demands, attentive to animal welfare, and consumption quality. This literature review aimed to house the most recent studies, which link circadian rhythm and photoperiod with zootechnical performance, welfare, immune system, and broilers' intestinal microbiota. Cementing a bilateral relationship between the intestinal microbiota and the immune system is directly influenced by light management.